2018
DOI: 10.1007/s11414-018-9588-9
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Age Divide: Cross-Age Collaboration Between Programs Serving Transition-Age Youth

Abstract: Programs that serve transition-age youth with serious mental health conditions typically reside in either the child or the adult system. Good service provision calls for interactions among these programs. The objective of this research was to discover programmatic characteristics that facilitate or impede collaboration with programs serving dissimilar age groups, among programs that serve transition-age youth. To examine this "cross-age collaboration," this research used social network analysis methods to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In 13 studies, networks were compared (e.g.,, partner strength) by geographic location (rural vs urban), funding, and population served. 106-116 Findings demonstrated that partnership strength including collaboration was lower in rural locations and low-resource settings or for those targeting different ethnic populations. Partnership strength was higher in networks with funding for partnership development.…”
Section: Resultsmentioning
confidence: 99%
“…In 13 studies, networks were compared (e.g.,, partner strength) by geographic location (rural vs urban), funding, and population served. 106-116 Findings demonstrated that partnership strength including collaboration was lower in rural locations and low-resource settings or for those targeting different ethnic populations. Partnership strength was higher in networks with funding for partnership development.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their complexity, US-style transition programs have been difficult to replicate locally or scale-up elsewhere (Paul et al 2015), and many have not been properly evaluated. Cross-age collaboration is higher in programs focusing on transition-age youth, compared to the child-only and adult-only programs (Davis et al 2018). A perception that funders want more cross-age collaboration appears to be positively associated with cross-age collaboration.…”
Section: Transition Program Modelmentioning
confidence: 90%
“…The number of programs providing support to transition-age youth only (primarily 16-25) is fewer in number. Apart from mental health support, the programs have provided a range of services, such as those linked to housing, independent living, vocational, substance abuse, education, recreation, and delinquency rehabilitation (Davis et al 2018).…”
Section: Transition Program Modelmentioning
confidence: 99%
“…The National Academy of Medicine specifically recommended that research be conducted to increase the number and availability of such evidence-based practices. Ellison et al, 2015;Geenen et al, 2015;Walker, Seibel, & Jackson, 2017), and population-, systems-, and provider-based rehabilitation research findings (e.g., Davis, Koroloff, Sabella, & Sarkis, 2018;Friesen et al, 2015;Walker & Flower, 2016).…”
Section: National Developments In the Fieldmentioning
confidence: 99%
“…The National Institute on Disability, Independent Living, and Rehabilitation Research and the Substance Abuse and Mental Health Services Administration (SAMHSA) cofunded two research centers focused on youth and young adults with serious mental health conditions in 2008 and again in 2014. The Pathways to Positive Futures (https://pathwaysrtc.pdx.edu/) and the Learning and Working During the Transition to Adulthood (https://www.umassmed.edu/TransitionsACR/research/projects-by-grant/rtc/) Rehabilitation Research and Training Centers, at Portland State University and the University of Massachusetts Medical School, respectively, have produced rehabilitation interventions (e.g., Ellison et al, 2015; Geenen et al, 2015; Walker, Seibel, & Jackson, 2017), and population-, systems-, and provider-based rehabilitation research findings (e.g., Davis, Koroloff, Sabella, & Sarkis, 2018; Friesen et al, 2015; Walker & Flower, 2016).…”
Section: National Developments In the Fieldmentioning
confidence: 99%